Biodiesel production from rubber seed oil using activated clinker as catalyst - Charan Kanwal, Chitra Charan Suri (2012)
This study uses clinker from the cement industry as a catalyst for transesterification of rubber seed oil to biodiesel.Clinker is nodules that are obtained from sintering limestone and aluminosilicate.Accordingly,there is a need to overcome depletion of fossil fuel,fluctuating price of edible oil which is used as biodiesel feedstock and expensive noble metals.The immediate objective of this research project is to synthesize catalyst from clinker for biodiesel production and to elucidate the mechanism of catalyst activation of the cement waste.Rubber seeds were collected,dried and shelled from the kernels.Microwave extraction was used to extract the rubber seed oil using hexane as the extraction solvent.Density of rubber seed oil was determined using density meter,calorific value using bomb calorimeter,acid test using potentiometer,FFA content and fatty acid methyl ester content using gas chromatography;all the test complied with ASTM D1480,D240, D664 and D 1983 for GC.Clinker collected from the conveyer belt was crushed using the jaw crusher to obtain clinker size of below 5mm.Crushed clinker was then grinded using mortar and pestle and was passed through 200 μm sieve. Mineral composition was analysed using XRF and surface area of clinker was found using Blaine apparatus.SEM analysis was done to study the activation and concluded the optimum activation parameter morphologically for transesterification.Clinker was activated at 64.7 °C under reflux for 1 hour with catalyst methanol ratio of 1:400 using catalyst loading determined through acid test of rubber seed oil with constant stirring at 400 rpm.Reaction was done under reflux at methanol boiling point, 60 ± 0.5 °C with constant stirring for 1 hour.After reaction,the reaction mixture was allowed to settle in a separating funnel overnight.The top layer (fatty acid methyl ester) was pipette out followed by the second layer (glycerol)The top layer was washed 3 times with distilled water to remove methanol and impurities.GC analysis was done for fatty acid methyl ester.Clinker was found to contain 66.61% of CaO and 2.7% free lime. Surface area is found to be 0.56 m2/g and acid number of FFA is 1.7952 mg KOH/g. Calorific value and density of FAME is 38.87 mJ/kg and 0.8548 g/cm3.The entire test done to date supports the use of clinker as a novel catalyst to produce biodiesel.